Production Performance of Wood Flour Reinforced Polymer Composites in Extrusion Process - Vanli, A. S.; Akdogan, A. (POLISH ACAD SCIENCES INST PHYSICS, 2018)
Wood flour reinforced polymer composites attract attention of the researchers and the market due to their visually aesthetic and low maintenance properties. Additive usage is an increasing application especially in wood flour reinforced polymer composite production for penetration into the new markets with more strong performance requirements and long-term stability interests. Since wood flour reinforced polymer composite materials need an efficient compounding process, extruders are specially designed as compounding types to overcome production difficulties and to supply high processing performance requirements. The experiments conducted in this work detail the steps of the production, such as process design and manufacturing and answer almost all required needs for continuous processing of wood flour reinforced polymer composite products. Higher processing capabilities and satisfactory mechanical test results were achieved with the help of pulping and compounding processes.
Keywords: FIBER; Physics